O Marcelim Tarnowskim — tłumaczu, redaktorze, księgarzu - Golda, Paweł; Ryszka, Joanna (2024)
The paper presents the biography of Marceli Tarnowski (1899–1942), a Polish translator of 145 books, bookseller editor, journalist, creator of the screenplay for the movie “Przybłęda”, and the author of an unfinished book about the Warsaw Ghetto. Tarnowski, who tragically died during World War II, was a member of the Bibliophiles’ Association in Łódź, the Polish Booksellers Association, and a co-founder of the Cooperative Booksellers Bank. The article provides an account of Tarnowski’s life and discusses his creative achievements, focusing on the numerous translations he wrote, including their reception and critique.
Keywords: Tarnowski, Marceli; Magórski, Andrzej